Cultural Communication in the Preservation of the Traditional Marine Education Values of the Mandar Tribe on Kerayaan Island - Syahlan Mattiro; Elly Malihah; Wahyu; Encep Syarief Nurdin; Hamsi Mansur (Jurnal Komunikasi Pendidikan, 2025)
Cultural communication plays an important role in maintaining and preserving the values of traditional marine education. In this context, cultural communication serves as a bridge to maintain traditional values while adapting them to the dynamics of the times in the era of modern life, especially the Mandar sailors on Kerayaan Island who have long been known for their maritime traditions inherent in their daily lives. This study aims to analyze the impact of modernization on the traditional practices and maritime cultural identity of the Mandar community. In addition, this study also presents the fact that not only the Bugis tribe is known as reliable sailors in the region, but the Mandar tribe also has a long history as accomplished sailors. The method used in the research uses a qualitative approach with the type of ethnographic research. The data was collected through direct observation in the field and in-depth interviews with local communities. Social change analysis is used as a theoretical framework to understand the maritime cultural transformation that occurs. This research shows that the entry of modern technology has slowly but surely changed the way of life of the Mandar seafaring community. Various cultural symbols that exist today are more widely used for economic purposes only, no longer as a cultural identity that is upheld. This study provides a real picture of how this change at least gives hope, that there will be no total death of traditional sized, there will always be adjustment, imaging and re-creation of new traditional authorities. The ability to survive this tradition is at least quite justified because the emergence of tradition always presupposes the presence of a 'regime of representatives' who has the authority to interpret the symbols and sacred texts of tradition for the purpose of legitimacy of power through cultural communication. Keywords: Mandar Tribe; Culture; Technological Modernization, Social Change